Influence of ‘Lactobacillus serum’ on the growth of Amaranthus hybridus and some soil chemical properties under screen house conditions - Ikponmwosa Ogbemudia; Valerie Ifeyinwa Ofili Edosa; Enameguono Ekpemuaka (Jurnal Ilmu Pertanian, 2022)
The potentials of lactic acid bacteria serum, termed as ‘Lactobacillus (LB) serum’, in enhancing soil nutrient availability and supplies for the growth of Amaranthus hybridus and some chemical properties of soil were investigated at the screen house of the Department of Soil Science, University of Benin. Three application rates of the serum were adopted, consisting of 3 mL (3,000 L.ha-1), 5 mL (5,000 L.ha-1), and 0 ml (0 L.ha-1), and represented as treatment. Amaranthus hybridus was transplanted into pots containing 2 kg of 2 mm sieved air-dried soil. Each treatment was replicated seven times to give a total of 21 pots that were laid out in a Completely Randomized Design (CRD). The treatments were applied twice a week starting from the 2nd week after transplanting. The plant growth indices measured were number of leaves, plant height and plant biomass. The results showed that serum positively influenced the number of leaves and plant biomass (4.333 kg to 4.830 kg) compared to the control (3.901 kg). However, the highest value of the plant biomass was found in the 3 mL (3,000 L.ha-1) treated pots, while the microbial colonies of bacteria in soil after serum application were sustained when compared with the control but at a reduced population for Bacillus subtilis. The application of LB. serum slightly improved the soil total organic carbon (320.0 g.kg-1 to 352.0 g.kg-1) and nitrogen (3.102 g.kg-1 to 3.325 g.kg-1) as against, 64.00 g.kg-1, and 0.639 g.kg-1 in the control respectively.